(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Innovative solutions that improve efficiency, precision, and safety have been made available as a result of the use of robots into food engineering, which has resulted in a transformation of the landscape of food manufacturing. Automated Processing and Handling, Vision Systems, and Collaborative Robotics (Cobots) are just few of the robotics approaches that are taken into consideration in this study, which undertakes an in-depth analysis of the numerous robotics techniques that are utilized in the sector. The success of each method is evaluated based on a number of criteria, such as its efficiency, accuracy, flexibility, safety, cost-effectiveness, ease of integration, and impact on the environment. Collaborative Robotics (Cobots) excel in safety and collaborative skills, while Vision Systems and Sensing Technologies emerge as leaders in precision and real-time quality control. Vision Systems and Sensing Technologies dominate the market. The study offers significant insights into the advantages and factors associated with each technique, so assisting industry stakeholders in making decisions that are informed and based on their particular operating requirements. The study highlights the dynamic nature of technology improvements and the necessity of a strategic strategy to harness robotics for optimizing food manufacturing processes. This occurs as the field continues to evolve, and the study highlights both of these aspects.